Voices of hard-to-reach island communities provide inclusive and culturally appropriate climate change responses: A case study from the Torres Strait Islands, Australia - Vinnitta Mosby; Bradley J. Moggridge; Sandra Creamer; Geoffrey Evans; Lillian Ireland; Gretta Pecl; Nina Lansbury (The Journal of Climate Change and Health)
abstract: Introduction: Many island-based Indigenous communities continue to occupy, manage and live off and from their ancestral lands. For some Indigenous Islander communities, climate change is already causing destruction to fragile ecosystems, affecting traditional food supply, and impacting on the health and livelihoods of communities. Materials and methods: The voices gathered through extended yarns of Torres Strait Islander Peoples was featured as a case study to describe the range of physical and psycho-social impacts from climatic changes to their Country, as well as their priority climate responses. Results & discussion: In describing climate change impacts and priority responses, Torres Strait Islander community members detailed five aspects of concern to them. These were to adequately monitor climatic changes and respond appropriately by drawing on Aboriginal and Torres Strait Islander Knowledges, to consider the human rights inherent in being protected from climate change, and to develop locally led solutions that are implemented soon. Conclusion: The impacts of climate change that are being seen and felt in Australia's Torres Strait Islands hold many similarities with small island nations in the Pacific whose islands are remote, climate-exposed, and their voices unheard on the political stage despite experiencing irreversible damage and gradual disappearance of their ancestral lands.